MANAJEMEN PERENCANAAN KEPALA SEKOLAH DI MTs ANWARUL HASANIYYAH - Faizah Faizah; Hamdiah Hamdiah; Helda Helda; Syahrani Syahrani (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
Planning management is a key aspect in principal leadership. The principal has a very important role in an educational institution. This research aims to determine the programs offered by school principals to improve the skills and planning of school principals in developing teacher productivity. This research uses quantitative research methods in the form of frequency distribution. The results of this research are: ideal learning planning based on the curriculum requirements that apply at the Mts Anwarul Hasaniyyah school, including the good category, appropriate strategies in developing learning programs that apply at the Mts Anwarul Hasaniyyah school, including the good category, problems and challenges in the applicable educational planning at the Mts Anwarul Hasaniyyah school it is included in the moderate or sufficient category.